Análise de confiabilidade estrutural utilizando o método FORM com múltiplos modos de falha para edifício alto submetido à ação do vento - Sakamoto, Beatriz Sayuri (2016)
The present work aims to apply structural reliability analysis to a tall building subjected to wind load considering human comfort in the evaluation of failure modes. For this purpose, the following random variables were considered: the maximum wind speed at the top of the building whose probability distribution is the Gumbel distribution for maximum and the modulus of elasticity of concrete with normal distribution. The analysis was conducted for two failure modes: excessive displacement on the top of the building, which is based on NBR 15575/2013, and the maximum acceleration for verification of the human comfort according to NBR 6123/2013. A joint analysis of failure modes applied in series was performed. The method used was the FORM - First Order Reliability Method with HLRF algorithm, implemented in Matlab environment, for the theoretical building CAARC. Large discrepancies between the failure probabilities of the two modes considered were found. For maximum acceleration, the design point value and the failure probability found were practical results. However, the horizontal displacement of 3 centimeters resulted in an extremely high probability of failure for low wind speed values, concluding that, for the tall building of the problem, the code limit tends to be easily extrapolated. Hence, the horizontal displacement parameter based on the total height of the building was also studied. Such analysis resulted in a failure probability greater than the acceleration one, however, presenting consistent design point values.